2022
DOI: 10.7759/cureus.21017
|View full text |Cite
|
Sign up to set email alerts
|

From Chest Wall Resection to Medical Management: The Continued Saga of Parapneumonic Effusion Management and Future Directions

Abstract: Pleural space infections have been described since the time of Hippocrates and to this day remains a significant pathology. Every year in the USA approximately there are one million hospital admissions for pneumonia with 20%-40% associated with some form of pleural space infections leading to pleural effusions with increased morbidity and mortality. Often, management of these effusions mandate combination of medical treatment and surgical drainage with debridement and decortication. There has been a lot of ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…A nationwide epidemiological analysis of pleural infections revealed that 64.9% of patients who underwent management with tube thoracostomy did not require a second therapeutic intervention [ 66 ]. However, surgical candidacy should be explored if patients are persistently septic despite chest tube drainage and antibiotics or if there is failure of chest tube drainage, antibiotics, and fibrinolytics [ 67 ]. Overall, surgical treatment is pursued in 36–65% of patients [ 6 ].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…A nationwide epidemiological analysis of pleural infections revealed that 64.9% of patients who underwent management with tube thoracostomy did not require a second therapeutic intervention [ 66 ]. However, surgical candidacy should be explored if patients are persistently septic despite chest tube drainage and antibiotics or if there is failure of chest tube drainage, antibiotics, and fibrinolytics [ 67 ]. Overall, surgical treatment is pursued in 36–65% of patients [ 6 ].…”
Section: Managementmentioning
confidence: 99%
“…There has been a substantial decrease in healthcare utilization, including inpatient use, length of stay, and costs over the past decade. Furthermore, inpatient mortality also decreased [ 67 ]. Thereafter, patient counseling on realistic prognosis based on clinical factors and response to initial interventions ensures aligned expectations and goals of care.…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
“…Based on thoracentesis results, parapneumonic effusion is categorized as either uncomplicated effusion, complicated effusion, or empyema. Across all three subtypes, morbidity and mortality rates are high, particularly among elderly and immunocompromised patients [3]. Mortality for patients with empyema reaches as high as 20%, and the need for eventual surgery is a similar 20% [4].…”
Section: Introductionmentioning
confidence: 99%
“…Однако между листками плевры присутствует небольшое количество жидкости, примерно 3-30 мл. Парапневмонический выпот -это вторичное накопление жидкости на фоне пневмонии, является ее наиболее частым осложнением и встречается в 57 % случаев инфекции легочной ткани [1]. Парапневмонический выпот, в зависимости от характера жидкости, разделяют на три типа: неосложненный, осложненный и эмпиема плевры.…”
unclassified
“…Плевральная жидкость при осложненном парапневмоническом выпоте нестерильная, содержит фибрин, в жидкости увеличивается количество нейтрофилов. Такой плевральный выпот не разрешится только на фоне антибиотикотерапии и возникает необходимость в дре- НАУЧНОЕ ОБОЗРЕНИЕ № 4, 2022   МЕДИЦИНСКИЕ НАУКИ  нировании плевральной полости, в ином случае осложненный парапневмонический выпот в короткие сроки трансформируется в эмпиему плевры [1].…”
unclassified